Case report: Novel DGUOK variants associated with idiopathic non-cirrhotic portal hypertension in a Han Chinese child - Li, Jia-Qi; Feng, Jia-Yan; Gong, Ying; Li, Wang-Qiang; Liu, Teng (Frontiers in Pediatrics, 2023)
DGUOK deficiency has primarily been associated with lethal hepatic failure with or without hypotonia, nystagmus, and psychomotor retardation, features typical of mitochondrial disease. A study in 3 Turkish children identified homozygosity for a variant in DGUOK as associated with idiopathic non-cirrhotic portal hypertension (INCPH). However, no further instances of INCPH associated with DGUOK variants have been reported. We here describe a fourth patient with DGUOK variants and childhood-onset INCPH, a 12-year-old Han Chinese boy, reporting clinical manifestations, histopathologic findings, and results of genetic studies. The child presented with hepatosplenomegaly; portal hypertension and hypersplenism were found. Vascular changes with hepatic fibrosis (Scheuer score 3) were observed on liver biopsy. Whole-exome sequencing and family analyses revealed compound heterozygosity for the DGUOK (NM_080916.3) variants c.778_781dup, (p.Thr261Serfs*28) and c.831_832del, (p.*278Thrfs*9) in the proband. These observations support ascription of instances of INCPH in children to variation in DGUOK.